Measurement of natural radioactivity in granites and its quartz-bearing gold at El-Fawakhir area (Central Eastern Desert), Egypt - M.A.M. Uosif; Shams A.M. Issa; L.M. Abd El-Salam (Journal of Radiation Research and Applied Sciences, 2015)
The distribution of natural radionuclides (226Ra, 232Th and 40K) in Granites and its quartz-bearing gold at El-Fawakhir area (Central Eastern Desert, Egypt) were measured by using γ-ray spectroscopy [NaI (Tl) 3″ × 3″]. X-Ray Fluorescence technique was used for chemical analyses of the studied samples. The specific activity of 226Ra, 232Th and 40K values are in range (3 ± 0.5 to 43 ± 2 Bqkg−1), (5 ± 0.7 to 41 ± 2 Bqkg−1) and (128 ± 6 to 682 ± 35 Bqkg−1) respectively. The absorbed dose rates ranged from 13.8 to 58.4 nGy h−1, where the total effective dose rates were determined to be between 16.7 and 70.9 μSvy−1. The maximum external hazard index (Hex) is 0.3 nGyh−1. The calculated values of the excess lifetime cancer risks (ELCR) and annual effective dose rate values are in between (8.48 × 10−5 and 2.63 × 10−4) and (24.2 and 72.9 μSvy−1) respectively. Geochemically, the studied granites consist of major oxides, they are characterized by SiO2, K2O, Na2O, Al2O3, and depleted in CaO, MgO, TiO2, and P2O5. The average absorbed dose rate (Do) in air is 37.8 nGyh−1 for the whole studied samples, this value is about 3.78% of the 1.0 mSvy−1 recommended by (ICRP-60,1991) to the public, so there is no radiological risk for the workers in that area.